Genomic Analysis Based on Chromosome-Level Genome Assembly Reveals an Expansion of Terpene Biosynthesis of Azadirachta indica - Du, Yuhui; Song, Wei; Yin, Zhiqiu; Wu, Shengbo; Liu, Jiaheng; Wang, Ning; Jin, Hua; Qiao, Jianjun; Huo, Yi-Xin (Frontiers in Plant Science, 2022)
Azadirachta indica (neem), an evergreen tree of the Meliaceae family, is a source of the potent biopesticide azadirachtin. The lack of a chromosome-level assembly impedes the understanding of in-depth genomic architecture and the comparative genomic analysis of A. indica. Here, a high-quality genome assembly of A. indica was constructed using a combination of data from Illumina, PacBio, and Hi-C technology, which is the first chromosome-scale genome assembly of A. indica. The genome size of A. indica is 281 Mb anchored to 14 chromosomes (contig N50=6 Mb and scaffold N50=19 Mb). The genome assembly contained 115 Mb repetitive elements and 25,767 protein-coding genes. Evolutional analysis revealed that A. indica didn’t experience any whole-genome duplication (WGD) event after the core eudicot γ event, but some genes and genome segment might undergo recent duplications. The secondary metabolite clusters, TPS genes, and CYP genes were also identified. Comparative genomic analysis revealed that most of the A. indica-specific TPS genes and CYP genes were located on the terpene-related clusters on chromosome 13. It is suggested that chromosome 13 may play an important role in the specific terpene biosynthesis of A. indica. And the gene duplication events may be responsible for the terpene biosynthesis expansion in A. indica. This will shed light on terpene biosynthesis in A. indica and facilitate comparative genomic research of the family Meliaceae.